Vestibular Nasal Body and Persistent Nasal Obstruction: Systematic Review (Revista de Medicina Clinica, 2022)
The nasal vestibular body is a structure that, on multiple occasions, goes unnoticed, and some authors have related it to situations of persistent nasal obstruction, even after surgical management, which is aimed at alignment of the nasal septum or turbinate reduction. . Given the low consideration of this small nasal region in the implications of refractory nasal obstruction, this review is born, on a region rarely evaluated and therefore not treated.
Keywords: Persistent Nasal Obstruction; Nasal Vestibular Body; Treatment